Key outcomes in treatment of activated phosphoinositide 3-kinase delta syndrome: An e-Delphi panel study and responder threshold application - Julia E. M. Upton; Kelli W. Williams; Andrew Cant; Ana Santos; João Bana e Costa; Jason Bradt; Amanda Harrington; Chad Gwaltney (PLoS ONE, 2025)
Background Activated phosphoinositide 3-kinase delta syndrome (APDS) is an ultra-rare, underrecognized inborn error of immunity. This study aimed to identify outcomes important in evaluating APDS treatment effectiveness and percent change in specific outcomes indicating a clinically meaningful benefit. Methods In this e-Delphi panel study, 28 globally based APDS experts used a 5-point Likert scale (Strongly Disagree to Strongly Agree) to indicate level of agreement that an outcome was an important measure of APDS treatment effectiveness in adult and pediatric patients at 3 and 6 months after treatment initiation. A threshold of ≥75% responding with “Agree” or “Strongly Agree” was considered consensus. Percent meaningful improvement in 6 outcomes was assessed and applied to APDS trial data (NCT02435173). Results Twenty-four panelists participated; e-Delphi rounds 1–5 were completed by 23, 21, 18, 17, and 16 panelists, respectively. Outcomes with the highest degree of consensus included lymph node size/volume, clinician overall impression of disease activity, antibiotic use, patient/caregiver-reported social outcomes and patient quality of life, hospitalizations, thrombocytopenia, spleen volume, lymphopenia, and anemia. Panelists indicated within-patient clinically meaningful improvements in adult patients ranged from median values of 20%−25% in lymph nodes, naïve B-cell to total B-cell ratio, spleen volume, hemoglobin, platelets, and lymphocytes at 3 months, and 25%−30% at 6 months. Panelists indicated within-patient clinically meaningful improvements in pediatric patients ranged from median values of 20%−27.5% at 3 months and 22.5%−45% at 6 months in the same 6 outcomes. In an application of responder thresholds, treatment with leniolisib resulted in significant and meaningful improvements in disease hallmarks, including lymph node size, spleen volume, and naïve B-cell ratio. Conclusion This study provides expert consensus on outcomes important in assessing APDS treatment effectiveness and improvement thresholds in 6 treatment outcomes indicative of a clinically meaningful benefit. These outcomes may help optimize APDS treatment in the clinic.